Penerapan model open Ended Learning untuk Meningkatkan aktivitas dan hasil belajar matematika pada materi operasi hitung bilangan Kelas IV MIN 1 Aceh Barat Daya - Suriani, Suriani (Universitas Serambi Mekkah, 2020)
Based on observations of the MIN 10 Aceh Barat Daya teacher's competence in compiling school action The purpose of this study is to improve the activities and learning outcomes of mathematics in the mate-rial arithmetic operations of fourth grade students MIN 1 Southwest Aceh. The study was conducted at MIN 1 Aceh Barat Daya. The model used in this study is the Open Ended Learning model. The subjects of this study were fourth grade students MIN 1 Southwest Aceh. The number of students is 33 students with a total of 16 male students and 17 female students. This research was conducted in the 2017/2018 school year within a period of 3 months, namely from August 2017 to October 2017 in the odd semester. The methodology of this research is Classroom Action Research (CAR) consists of two cycles and each cycle consists of two meetings. Each cycle consists of planning, implementing, observing and reflecting. The research procedure consisted of pre-research, planning cycle one, implementing cycle one, observ-ing cycle one, reflection cycle one, planning cycle two, implementing cycle action two, observing cycle two and reflection cycle two. Data collection technique is to collect the value of the test carried out at the end of each learning in each cycle using the question instrument (written test). Observation data is done by observing the activeness of students' learning processes. Data were analyzed by means of per-centage statistics. Data were analyzed by means of percentage statistics. The results showed that an in-crease in completeness of student learning outcomes from 39.39% in the pre-study increased to 60.60% in the first cycle and increased to 84.84% in the second cycle. Student learning activities have increased from enough categories to be good and good categories increased to very good. Based on the description that has been stated above, it can be concluded that the application of the Open Ended Learning model can improve the activities and learning outcomes of mathematics in the material arithmetic operations of fourth grade students MIN 1 Southwest Aceh 2017/2018 Academic Year. in cycle I was 76.50 (Good) increased to 87.16 (Very Good) in cycle II with an increase of 10.66 points.